Character Building Strategies in Vocational Schools: The Contribution of PAI and Character Education Teachers to Student Character - Dina Safitri Yuri; Samima Nasrin; Andelina Damayanti; Amilia Mariam Ulfa; Salsabila Ariyani (Cultura Islamica: Journal of Islamic Studies, Management, and Culture, 2026)
This study examines the role of PAI and Character Education teachers in the development of student character in vocational schools, specifically at SMK Negeri 1 Terusan Nunyai Lampung Tengah. Using a descriptive qualitative approach, this study explores how the pedagogical role of teachers contributes to the development of students' moral and ethical values. The study highlights the strategies employed by teachers in instilling values such as discipline, responsibility, and social care, as well as the challenges faced in character development in vocational schools. The findings show that character development is more effective when teachers integrate religious and moral values into the curriculum and reinforce behavior through consistent school routines such as religious activities and extracurricular programs. The role of the teacher is not limited to teaching content, but also as a moral guide, role model, and facilitator of a positive school culture. The study identifies key supporting factors such as school support, communication between teachers and students, and the consistency of religious programs, as well as barriers from the influence of social environments and media. This study contributes to the understanding of how vocational schools can effectively integrate character education into academic programs and provides practical recommendations to improve teaching strategies in PAI and Character Education.